Sistem Pendukung Keputusan Menentukan Bibit Padi Terbaik Menggunakan Metode Gap Kompetensi - Elvis Pawan; Agung Jasuma; Achmad Yusron Arif; Kusrini Kusrini (SISFOTENIKA, 2020)
Government is preparing Indonesia to achieve food self-sufficiency, but we need know the main process that will hamper these ideals achieved if the production of paddy agriculture decreases, especially remote areas. This is due to lack of knowledge of farmers in determining which rice seeds are suitable for planting on agricultural land. This research is expected to help farmers specifically who do not understand the determination of good rice seeds. In addition, the results of this study can help the government realize food self-sufficiency in Indonesia. In designing this SPK using the Competence Gap method by including several criteria such as rice production per hectare, disease resistance, seed prices, planting limits, and land requirements, these criteria will be processed according to the rules of the Competence Gap method to produce the best seed recommendation. This study resulted in SPK, the main criteria used for disease resistance and the price of seeds given a priority value of 70%, another criterion of 30%. Based these criteria, three rice varieties recommended by DSS, Kalimasada, both Inpasari 42 GSR and the three types of Mapan P-05. The next researcher expected able to compare several methods and combine them into expert system for better accuracy.